The Eden-Eisenhower correspondence : 1955 - 1957 - Eden, Anthony, 1897-1977 1897-1977 (Univ. of North Carolina Press, 2005)
"The personal correspondence between President Dwight D. Eisenhower and Prime Minister Anthony Eden during the time they were simultaneously in office tells the dramatic story of a relationship that began with great promise but ended in division and estrangement." "The connection between the two leaders, which had been forged during World War II, was reflected in their decision to continue writing to each other on a personal level in addition to normal government communications, a practice that Eisenhower had also followed with Winston Churchill. The first year of their correspondence indicates a strong bond between Eden and Eisenhower. The Suez crisis of July 1956, however, soured relations between them, as Eden argued for the use of force and Eisenhower insisted on a peaceful approach to resolving the conflict. Their differences are spelled out with remarkable eloquence and depth of analysis in the letters, in a way that could not be found in any other source." "Many of the letters have only recently been declassified, making it possible for the first time to publish this unique historic collection in its entirety."--BOOK JACKET.